Comparison of Enzyme Secretion and Ferulic Acid Production by Escherichia coli Expressing Different Lactobacillus Feruloyl Esterases - Xu, Zhenshang; Kong, Jian; Zhang, Susu; Wang, Ting; Liu, Xinli (Frontiers in Microbiology, 2020)
Construction of recombinant Escherichia coli strains carrying feruloyl esterase genes for secretory expression offers an attractive way to facilitate enzyme purification and one-step production of ferulic acid from agricultural waste. A total of 10 feruloyl esterases derived from nine Lactobacillus species were expressed in E. coli BL21 (DE3) to investigate their secretion and ferulic acid production. Extracellular activity determination showed all these Lactobacillus feruloyl esterases could be secreted out of E. coli cells. However, protein analysis indicated that they could be classified as three types. The first type presented a low secretion level, including feruloyl esterases derived from Lactobacillus acidophilus and Lactobacillus johnsonii. The second type showed a high secretion level, including feruloyl esterases derived from Lactobacillus amylovorus, Lactobacillus crispatus, Lactobacillus gasseri, and Lactobacillus helveticus. The third type also behaved a high secretion level but easy degradation, including feruloyl esterases derived from Lactobacillus farciminis, Lactobacillus fermentum, and Lactobacillus reuteri. Moreover, these recombinant E. coli strains could directly release ferulic acid from agricultural waste. The highest yield was 140 μg on the basis of 0.1 g de-starched wheat bran by using E. coli expressed L. amylovorus feruloyl esterase. These results provided a solid basis for the production of feruloyl esterase and ferulic acid.